(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1862)
The author suggests that a brass coin found in the River Jed belongs to the reign of the Northumbrian King Osbrecht. However, he does acknowledge that coins relating to this king are rare and notes some stylistic differences between this coin and other examples from the period. The article concludes with a brief explanation of the importance of this type of coin to Anglo-Saxon numismatics.